2019
DOI: 10.1136/vetreco-2019-000344
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of histopathology and locations of excised eyelid masses in dogs

Abstract: BackgroundEyelid masses are the most common ocular diseases in dogs. However, there are no studies specifically investigating the location of eyelid masses.Methods118 dogs with 119 eyelid masses were included. Medical records and pathology reports were retrospectively reviewed at National Taiwan University veterinary hospital and Vision Eyecare Centre for Animals between 2012 and 2017.ResultsMean age of dogs was 9.4±2.5 years. Female spayed dogs had significantly higher prevalence of eyelid mass than female in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Beagle, Siberian Husky, English Setter, Toy and Miniature Poodle, Labrador Retriever, and Golden Retriever were identified as breeds susceptible to developing these tumours [ 20 ]. All of these breeds are represented in our study, although epidemiological studies correlating the incidence of the pathology with the breed are still lacking [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beagle, Siberian Husky, English Setter, Toy and Miniature Poodle, Labrador Retriever, and Golden Retriever were identified as breeds susceptible to developing these tumours [ 20 ]. All of these breeds are represented in our study, although epidemiological studies correlating the incidence of the pathology with the breed are still lacking [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 73% of eye neoplasms in canine species are benign [ 21 , 25 ]. In our study, we found that the most frequent eyelid tumours were neoplasms of the meibomian glands, as previously reported in reference [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Additionally, chronic inflammatory diseases of the ocular surface, such as graft-versus-host disease and Stevens-Johnson syndrome, can cause the development of MGD in humans. 17,18 In dogs, the clinical excision of meibomian gland adenomas, 19,20 epitheliomas, 21,22 and distichiae 23 have been reported to affect the meibomian glands. Some of these studies investigated the impacts of the procedures on the tear film reporting no effect on the tear film 19 or a decrease in tear film breakup time (TFBUT, see Section 4.1.1).…”
Section: Secondarymentioning
confidence: 99%